Parental Socioeconomic Status, Communication, and Children's Vocabulary Development: A Third‐Generation Test of the Family Investment Model. Issue 3 (30th November 2012) - Sohr‐Preston, Sara L.; Scaramella, Laura V.; Martin, Monica J.; Neppl, Tricia K.; Ontai, Lenna; Conger, Rand
<x xml:space="preserve">Abstract</x> This third‐generation, longitudinal study evaluated a family investment perspective on family socioeconomic status (SES), parental investments in children, and child development. The theoretical framework was tested for first‐generation parents (G1), their children (G2), and the children of the second generation (G3). G1 SES was expected to predict clear and responsive parental communication. Parental investments were expected to predict educational attainment and parenting for G2 and vocabulary development for G3. For the 139 families in the study, data were collected when G2 were adolescents and early adults and their oldest biological child (G3) was 3–4 years of age. The results demonstrate the importance of SES and parental investments for the development of children and adolescents across multiple generations.